2020
DOI: 10.4049/jimmunol.2000185
|View full text |Cite|
|
Sign up to set email alerts
|

Hypoxia-Inducible Factor α Subunits Regulate Tie2-Expressing Macrophages That Influence Tumor Oxygen and Perfusion in Murine Breast Cancer

Abstract: Tie2-expressing monocytes/macrophages (TEMs) are a distinct subset of proangiogenic monocytes selectively recruited to tumors in breast cancer. Because of the hypoxic nature of solid tumors, we investigated if oxygen, via hypoxia-inducible transcription factors HIF-1a and HIF-2a, regulates TEM function in the hypoxic tumor microenvironment. We orthotopically implanted PyMT breast tumor cells into the mammary fat pads of syngeneic LysMcre, HIF-1a fl/fl /LysMcre, or HIF-2a fl/fl /LysMcre mice and evaluated the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 51 publications
1
24
1
Order By: Relevance
“…As previously discussed in this review ( Figure 2 ), TEMs play a role in angiogenesis; however, in the setting of cancer, where the number of TEMs is elevated, TEMs are responsible for aberrant and dysfunctional angiogenesis [ 53 ]. In the transgenic rat insulin promoter (RIP)-T antigen (Tag) murine model of metastatic pancreatic neuroendocrine tumor (PNET), which causes carcinogenesis of β-cells of the pancreas and is commonly used to study tumor angiogenesis [ 135 ], inhibition of TIE2 on TEMs reduces TIE2 + myeloid infiltration resulting in reduced microvessel density, less vascular permeability, and blockade of tumor cell intravasation mediated by TIE2 Hi /VEGF-A Hi macrophages [ 136 ].…”
Section: Sequelae Of Macrophages and Neutrophils In Pdacmentioning
confidence: 99%
See 3 more Smart Citations
“…As previously discussed in this review ( Figure 2 ), TEMs play a role in angiogenesis; however, in the setting of cancer, where the number of TEMs is elevated, TEMs are responsible for aberrant and dysfunctional angiogenesis [ 53 ]. In the transgenic rat insulin promoter (RIP)-T antigen (Tag) murine model of metastatic pancreatic neuroendocrine tumor (PNET), which causes carcinogenesis of β-cells of the pancreas and is commonly used to study tumor angiogenesis [ 135 ], inhibition of TIE2 on TEMs reduces TIE2 + myeloid infiltration resulting in reduced microvessel density, less vascular permeability, and blockade of tumor cell intravasation mediated by TIE2 Hi /VEGF-A Hi macrophages [ 136 ].…”
Section: Sequelae Of Macrophages and Neutrophils In Pdacmentioning
confidence: 99%
“…We recently reported that in a PyMT mouse model of breast cancer, breast tumors containing wild type and HIF-2α-deficient macrophages (containing only HIF-1α) had elevated numbers of tumor TEMs, increased hypoxia, and poor vessel perfusion that limited docetaxel delivery and efficacy. Mice with macrophages containing only HIF-2α (HIF-1α-deficient) had a reduced number of TEMs, better vascular architecture, and increased oxygen that enabled better perfusion and enhanced tumor cytotoxicity [ 53 ]. Like TEMs, a subset of neutrophils has been shown to express TIE2 [ 75 , 76 ].…”
Section: Sequelae Of Macrophages and Neutrophils In Pdacmentioning
confidence: 99%
See 2 more Smart Citations
“…Hypoxia, or lack of oxygen, is a characteristic feature of most solid tumor [6]. Increasing evidence has found that the hypoxic environment in tumors directly stimulated the malignant properties of cancers, including advanced aggressiveness and resistance to therapies [7][8][9][10]. Meanwhile, the in ltration of immune cells in the tumor is also a crucial component that can affect the tumor invasion and metastasis [11].…”
mentioning
confidence: 99%